Applications of acoustics and cavitation to noninvasive therapy and drug delivery - Coussios, C; Roy, R (2008)
Biomedical acoustics is rapidly evolving from a diagnostic modality to a therapeutic tool, and acoustic cavitation is often the common denominator in a wide range of new therapeutic applications. High-intensity focused ultrasound (HIFU) waves generated outside the body can be used to deposit heat deep within the body. Through a quantitative analysis of heat deposition by ulrasound, it is shown that inertial cavitation can help address some of the major challenges of HIFU therapy by providing a means of enhancing and monitoring treatment noninvasively. In the context of drug delivery, both inertial and stable cavitation play rates in enhancing drug activity and uptake. In particular, shape oscillations arising during stable cavitation provide an effective micropumping mechanism for enhanced mass transport across inaccessible interfaces. Copyright © 2008 by Annual Reviews. All rights reserved.